The role of parental Math anxiety in students’ Math anxiety and performance - Sarıgül, Samet. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
The current study mainly aims to clarify parental roles in students’ math anxiety and performance. The relationship between anxiety and achievement has been widely studied and negative correlation was found (Hembree, 1990; Erktin et al, 2006; Devine et al., 2012). Identifying patterns of interaction between anxiety and performance along with parental involvement is at the focus. Parent-child relationship concerning anxiety was hypothesized to be grounded by control-value theory, dealing with roles of control and value appraisals in achievement emotions (Pekrun, 2006). The study was structurally planned in two phases. The first phase comprised of data collection from 335 students and their parents on measures of math anxiety, students’ performance, parental involvement, subjective appraisals. The results indicated that both students’ and parents’ anxiety was negatively correlated with students’ achievement. Students’ and parents’ anxiety was found to be positively correlated. Regression analysis showed that 36% of the variance in achievement can be explained by students’ anxiety and their subjective control. 48% of the variance in students’ anxiety can be predicted by parents’ anxiety, control appraisals of both and achievement. In the second phase, 12 of the most anxious children and their parents were interviewed. Analysis of the interviews showed that parent-child contact concerning math anxiety, as an academic emotion, can be explained by control-value theory. Parental expectations and overvaluing were emerged as prominent contributors of anxiety induced by parents. The results were discussed in terms of justifying the development of clues to teachers about promoting parental involvement, aiming at increased students’ learning.
Keywords: Math anxiety.